East Timor as an important source of cashew (Anacardium occidentale L.) genetic diversity - Guterres, Lara (2023)
Background. Cashew (Anacardium occidentale L.) is a crop currently grown in several tropical countries because of the economic importance of cashew nuts. Despite its enormous economic worth, limited research has been conducted on the molecular diversity of cashew genetic resources. In this study, a wide comprehensive assessment of the genetic diversity of cashew trees in East Timor was performed using microsatellites (SSRs) to evaluate intraspecific diversity and population structuring. Methods. A total of 207 individual cashew trees, including trees from East Timor (11), and outgroup populations from Indonesia (one) and Mozambique (two), were analyzed with 16 cashew-specific SSRs. A comprehensive sampling of cashew trees within East Timor was performed, covering the distribution of cashew orchards in the country. Genetic diversity indices were calculated, and population structuring was determined using three different approaches: genetic distances (UPGMA and NJ), AMOVA, and individual-based clustering methods through Bayesian (STRUCTURE) and multivariate (DAPC) analyses. Results. The population structuring analysis revealed that the genetic diversity of cashew populations in East Timor was higher in this study than previously reported for cashew trees. A higher allelic richness was found within cashew populations in East Timor compared with the outgroup populations (Mozambique and Indonesia), reinforced by the presence of private alleles. Moreover, our study showed that cashew populations in East Timor are grouped into two dissimilar genetic groups, which may suggest multiple cashew introductions over time. These new cashew genetic resources could be explored for future crop improvement. Conclusions. Crop diversity underpins the productivity, resilience, and adaptive capacity of agriculture. Therefore, this study provides useful information regarding genetic diversity and population structure that can be harnessed to improve cashew production in East Timor. This data is also important to creating a country-specific genetic cashew signature to increase cashew market value.